Slavery, the State, and Islam: By Mohammed Ennaji; trans. Teresa Lavender Fagan (Cambridge: Cambridge University Press, 2013. 260 pages.) (American Journal of Islam and Society, 2015)
Slavery, the State, and Islam is Fagan’s English rendering of Mohammed Ennaji’s2007 work Le Sujet et le Mamelouk: Esclavage, Pouvoir et Religion dansle Monde Arab, a historical study of the economics of power in the relationshipamong slavery, Islam, and monarchy. Ennaji investigates the structure and natureof the “bond of authority” as it manifests itself in servitude between theking and subject, master and slave, God and believers. The bulk of his primaryhistorical material belongs to the first few centuries of Islam. However his intention,as he notes in the introduction, is to also make sense of contemporarymodes of power that govern the scene of authority in the individuals’ proximityto the state and, in some instances, to one another.The opening chapter tells an anecdote of a nineteenth-century Moroccanofficial who was stripped of his title as Local Governor (in Arabic, Qaid), declareddead to the public, and kept as a slave in the sultan’s palace. Ennajichallenges the official narrative and weaves novel threads of the story to showthe degree to which the bond of authority between the sultan and his servantsdepends upon uninterrupted flat obedience.The second chapter questions the issue of slavery during Islam’s earlyyears. The author claims that the new religion made little practical changes tothis institution and, in certain cases, made slaves even more abjectly submissiveto their masters. Ennaji particularly details Islam’s termination of the statusesof sa’b (a sā’ib is a slave who has attained full unconditional freedom) andṭalq (repudiation) and its admission of mawlā (freed slaves must remain loyalto their ex-master). He also elaborates on the non-provision of part of the publicfunds to free more slaves, as well as the practice of depriving freed slaves ofthe spoils of war and discouraging people from marrying them.In the third chapter, Ennaji undertakes the king-subject relation in lightof the notion of servitude. He probes the sociolinguistic roots of several conceptualizations,including ‘ibādah, ra’īyah, and ṭā‘ah (translated successivelyas adoration, people, and obedience). He also examines the semiotics of variousexpressions of servitude and presents a prolonged discussion of the differentuses of the hand in this context. Ennaji contends that the transition toIslam barely changed anything in the structure of authority and the masterslaverelationship. As he puts it, with the advent of Islam there was “a reorganizationof the authoritarian space that reshuffled the division of powerbetween the king and the divine authority” (p. 82). This redistribution of poweris elaborated in the fourth chapter, where the author draws on concepts used ...